2019
DOI: 10.1159/000498887
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Temozolomide-Capecitabine to 5-Fluorouracile-Dacarbazine in 247 Patients with Advanced Digestive Neuroendocrine Tumors Using Propensity Score Analyses

Abstract: Introduction: Although chemotherapy combining 5-fluorouracil (5FU)-dacarbazine (DTIC) or temozolomide (TEM)-capecitabine (CAP) is extensively used in patients with neuroendocrine tumors (NET), they were never compared. We compared their tolerance and efficacy in advanced NET. Methods: We evaluated the records of consecutive patients with pancreatic or small-intestine advanced NET who received 5FU-DTIC or TEM-CAP between July 2004 and December 2017 in 5 French centers. Tolerance, tumor response and progression-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…Additionally, de Mestier and colleagues (2019) compared CAPTEM with 5-fluorouracil (5FU)-dacarbazine (DTIC) in 247 patients with NEN. It was found that PFS was similar between the two groups 13.9 vs. 18.3 months, p = 0.86) [31]. Parallel to Chatzellis' study, the majority of patients getting CAPTEM had a pNEN primary disease (82.3%), and only 27 patients with non-pNENs.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Additionally, de Mestier and colleagues (2019) compared CAPTEM with 5-fluorouracil (5FU)-dacarbazine (DTIC) in 247 patients with NEN. It was found that PFS was similar between the two groups 13.9 vs. 18.3 months, p = 0.86) [31]. Parallel to Chatzellis' study, the majority of patients getting CAPTEM had a pNEN primary disease (82.3%), and only 27 patients with non-pNENs.…”
Section: Discussionsupporting
confidence: 51%
“…Parallel to Chatzellis' study, the majority of patients getting CAPTEM had a pNEN primary disease (82.3%), and only 27 patients with non-pNENs. In this study, the use of CAPTEM in pNET was associated with a significantly higher ORR, PFS, and OS when compared to patients with non-pNENs [30,31].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Papaxoinis et al 49 de Mestier et al 50 registered. Reoperation was required in 5.9%, renal dysfunction was observed in 3% of cases, biliary dysfunction-in 3.6%, and death-in 1.2%.…”
Section: Capecitabine/ Temozolomidementioning
confidence: 96%
“…The most widely used chemotherapy regimens in PanNETs rely on alkylating agents, such as streptozotocin (STZ) (combined with 5-fluorouracil (5FU) or doxorubicin (Dilz et al 2015, Clewemar Antonodimitrakis et al 2016), dacarbazine (DTIC) (alone or combined with 5FU (Walter et al 2015, de Mestier et al 2019) and its oral prodrug temozolomide (TMZ) (alone or combined with capecitabine (CAP) (Koumarianou et al 2015, de Mestier et al 2020b. However, chemotherapy has been scarcely compared to other therapeutic options yet.…”
Section: Introductionmentioning
confidence: 99%